LGG-28. Rapid symptomatic improvement for a patient treated with BRAF inhibition for BRAFV600E mutated ganglioglioma. (3rd June 2022) - Cantor, Evan; Cochrane, Anne; Morris, Stephanie; Meyer, Ashley; Ogle, Andrea; Shatara, Margaret; Cluster, Andrew; Deng, Mai; Abdelbaki, Mohamed S; Brossier, Nicole M
Abstract: BACKGROUND: Biologically targeted agents such as the BRAF inhibitor dabrafenib are now used to treat progressive low-grade glioma (LGG), but the effect of these agents on the neurologic symptoms that accompany LGGs is poorly understood. CASE: A 21-year-old male was diagnosed with medullary ganglioglioma (GG) after presenting with persistent vertigo and positional headaches. Immunohistochemistry was consistent with BRAF V600E mutation and dabrafenib was started. The patient had resolution of his neurologic symptoms within 3 weeks of treatment initiation; surveillance MRI several months later demonstrated interval decrease in tumor size. The patient remained on therapy for 2 years. Several days after planned drug discontinuation the patient had re-emergence of persistent vertigo that impaired his ability to work. Repeat imaging two months later demonstrated an increase in tumor size and solid enhancement along tumor margins. He was restarted on dabrafenib. Within one week, he again had complete resolution of his vertigo. DISCUSSION: Gangliogliomas are comprised of mixed neuronal and glial components and associated with epilepsy, headache and other localizing neurologic symptoms. In this report, we describe clinical and radiographic response from single-therapy dabrafenib in a patient with BRAF V600E+ GG, along with a very rapid resolution of neurologic symptoms upon initiation of the drug and recrudescence shortly following cessation of therapy. The symptoms subsided within a week of restarting dabrafenib, suggesting a separate, more rapid mechanism of symptom reversal than decline in tumor size. BRAF mutations have been identified in both the neuronal and glial components of ganglioglioma, suggesting that dabrafenib may provide symptomatic relief via inhibition of abberant neuronal processes. CONCLUSION: BRAF inhibitors can rapidly improve neurological symptoms via a rapid, not yet fully elucidated mechanism. Kinetics of this response suggest it is independent of effects on tumor volume and the degree of compression to tissue surrounding the tumor.